MENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP BHAKTI MULYA BATUJAJAR KELAS VII MENGGUNAKAN PENDEKATAN SAINTIFIK - Ainaya, Fina; Pertiwi, Citra Megiana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This research is a classroom action research (CAR) with the main objective of improving students' Mathematical Comprehension Ability (KPM) in algebraic form with the help of the application of a scientific approach. This research is motivated by the lack of student KPM in learning mathematics. This CAR is carried out with research stages including (1) Planning (Planning), (2) Action (Acting), (3) Observing (Observing) and (4) Reflecting (Reflecting). This study has a subject, namely 16 students in class VII C SMP Bhakti Mulya Batujajar with data collection techniques through pretest and posttest in the form of 6 questions, teacher observation sheets and student observation sheets. The implementation of this research is for 2 cycles consisting of 4 meetings. Data analysis was carried out quantitatively and qualitatively. So the result of this research is that the student's KPM in the first and second cycles increased by 18.75% where in the first cycle students' learning completeness was 68.75% in the second cycle to 87.5%. So it can be concluded that, KPM in learning mathematics can be improved with the help of the application of a scientific approach.